Multidimensional on-site perception study of stairway spaces in mountain city parks among young and older adult people: a case study of Pipa Mountain Park, Chongqing, China - Cong Gong; Cong Gong; Xinyu Yang; Changjuan Hu; Changjuan Hu; Zhenkun Mao (Frontiers in Psychology)
Stairway spaces in mountain city parks are crucial for vertical traffic. The multidimensional perceptions of stairway spaces are influenced by visual and auditory environments and behavioural traits. The intrinsic associations between environmental factors and age have been universally confirmed using multimodal data; however, localised studies on the perceptions of different age groups in mountainous environments are lacking. Thus, a pilot study was conducted in a mountain city park stairway space in Yuzhong District, Chongqing, China. Controlled environmental variables and real-time measurements of the psychological and physiological perceptions of young and older adult individuals were analysed using summary statistical descriptions of physiological data, Spearman’s correlation analysis for consistency assessment, and a generalised linear mixed model. The influence of eight visual and three auditory environmental factors on physiological perceptions at various nodes along the paths was assessed. Results revealed significant psychological differences between young and older adult individuals on uphill stairway paths. Young participants exhibited higher consistency between psychological and physiological perceptions and more positive psychological responses. Both groups perceived greater stress on long stairway paths than on short ones. The elevation difference, green slope ratio, and openness majorly affected the physiological changes in both groups. These results can guide future stairway space enhancements.